2021
DOI: 10.18280/ria.350503
|View full text |Cite
|
Sign up to set email alerts
|

A Precision Agricultural Application: Manggis Fruit Classification Using Hybrid Deep Learning

Abstract: Fruits come in different variants and subspecies. While some subspecies of fruits can be easily differentiated, others may require an expertness to differentiate them. Although farmers rely on the traditional methods to identify and classify fruit types, the methods are prone to so many challenges. Training a machine to identify and classify fruit types in place of traditional methods can ensure precision fruit classification. By taking advantage of the state-of-the-art image recognition techniques, we approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…For example, the first article addressed the classification of mangosteen fruits using an optimized CNN model using the Adam optimizer, achieving improvements in the accuracy of the results. (7) Other studies also explored different optimizers as shown in table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the first article addressed the classification of mangosteen fruits using an optimized CNN model using the Adam optimizer, achieving improvements in the accuracy of the results. (7) Other studies also explored different optimizers as shown in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Sumari et al (7) Vasumathi et al (8) Nasir et al (9) Palakodati et al (10) Siddiqi (11) N e u r a l Networks Used On the other hand, when analyzing the articles, it was observed that some focused on the classification of a single specific fruit, such as dragon fruits. (4) However, there were also studies that addressed the classification of various types of fruits, as shown in table 3.…”
Section: Table 2 Optimizers Used In Some Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple classifier combination goals to achieve the final decision by integrating the predictions of several individual classifiers to obtain comprehensive results. Experimental studies have shown that the combination of several classifiers has been very helpful in improving the classification accuracy [2], [3] There are several ensemble and deep learning methods for fruit classification have been proposed [4]- [7]. However, deep learning in machine learning uses large amounts of data.…”
Section: Introductionmentioning
confidence: 99%